Hydro-thermal priming enhance seed germination capacity and seedling growth in sugar beet - Alipor, Shima; Taghvaei, Mansour; Jalilian, Ali; Kazemeini, Abdolreza; Razi, Hooman (Cellular and Molecular Biology, 2019)
Seed priming improves seed performance in many crop species. In this study, the influence of hydrothermal priming on seed parameters of sugar beet is investigated in both laboratory and field conditions. In the laboratory, the treatments consist of a combination of cultivars (Arya and Shokoofa), hydro-priming at two temperatures (10 and 15 °C) for 6, 10, 14, 18, 22 hours. Germination traits and seedling growth were measured for determination of optimum hydro-thermal priming. Also, the protein pattern in the optimum hydro-thermal priming treatments and unprimed seeds were compared by electrophoresis. In the field experiment, the percentage and rate of emergence of primed and unprimed seeds were measured. Results showed that hydro-thermal priming had a positive effect on final germination percentage, mean germination time and uniformity of germination. Optimum hydro-thermal priming time and the temperature were 6 and 10 hours at 15 °C for Shokoofa and Arya cultivars respectively. Hydro-thermal priming increased the seed emergence percentage in the field by 15%. There was no significant difference in protein pattern between primed and unprimed seeds. In general, hydro-thermal priming not only increases sugar beet seed germination in the laboratory but also has a more positive effect on the emergence in the field condition.